Dialética da cordialidade: afinidades eletivas benjaminianas no pensamento político e social de Sérgio Buarque de Holanda - Ramirez, Paulo Niccoli (2007)
The present dissertation targets the investigation and reconstruction of some of Sérgio Buarque de Holanda's and Walter Benjamin's main concerns, seeking the elective affinities, or convergences, which find their most striking correspondence in the cordiality topic. As the central hypothesis for studying the dialectics of cordiality, we find that the use of allegories, metaphors, and dialectical images, among other important matrixes which are present in several Walter Benjamin's writings, convenes for existing issues in Sérgio Buarque de Holanda's Raízes do Brasil and Visão do Paraíso, allowing it to detect major elective affinities between both authors. Those go from a narrative, fragmentary style to the criticism and overcoming necessity both of historical versions and domination forms and practices present in the Brazilian social and political trajectory. When taken in its dialectical sense, cordiality may be read as an existing powerful allegory in SBH's thinking, once it points out the understanding of the Brazilian societal configuration's political and cultural features